Women, Equality and Education: A model of person and society in 1st century Christian writings - Jiménez Ríos, Francisco Javier; Martínez-Heredia, Nazaret; Amaro Agudo, Ana; González-Gijón, Gracia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the stories of Mary, the mother of Jesus, we find a model of human personal reality in the dynamism of its realisation as a continuous being-as-self that shows its overflowing as an educating reality, an open reality. In other accounts, women are shown as witnesses to the encounter with Jesus after his death, a testimony that is received by Jesus’ group and corroborated by the men of the community in order to reach beyond its borders. In the testimony received and the action shared, the foundations of a society that is built on equality are shown.